Evaluation of Lymph Node Biopsies in a Peripheral Tertiary Hospital (KYAMC Journal, 2017)
Background: Lymphadenopathy is a common clinical condition in Bangladesh and histopathological examination is important for diagnosis.Objectives: The aim of this study was to detect pattern of benign and malignant conditions of lymphadenopathy.Methods: This study was done in the department of Pathology, Khwaja Yunus Ali Medical College & Hospital (KYAMCH), a rural tertiary hospital in Bangladesh. A total of 420 lymph node biopsies from January 2013 to December 2015 were included.Results: Among these, 208 (49.5%) were metastatic carcinoma, followed by non-specific lymphadenitis 116 (27.6%), non-hodgkin lymphoma 48 (11.4%) and tuberculosis 35 (8.3%). The mean age±SD of patients was 44.82±15.42 years. Incidence of malignancy was quite higher in compare to previous studies.Conclusion: In case of any suspicious lymphadenopathy, histopathology should be done for diagnosis and also to exclude malignancy that will help to reduce patients' morbidity and mortality.KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 49-52